Effect of bacterial inoculants on the fermentation and preservation efficiencies and nutritive value of alfalfa silage for growing steers - Bolsen, K.K.; Huck, G.L.; Siefers, M.K.; Turner, J.E.; Anderson, S.A.; Pendergraft, J.S.; Young, Matthew A.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two silage bacterial inoculants from Pioneer Hi-Bred International, Inc. were evaluated using second-cutting alfalfa. The Pioneer brand 1174® inoculant and a Pioneer experimental inoculant each increased the rate and efficiency of the ensiling process in both farm-scale and laboratory-scale silos. The two inoculants increase d the DM recovery in the farm-scale silos compared to the untreated silage. Steers fed the experimental inoculant-treated silage gained faster (P<. 10) (2.56 vs. 2.37 lb per day), had a 4.0% higher DM intake, and were 4.3% more efficient than steers fed the untreated silage. The 1174-treated silage supported a numerically but not statistically better steer performance than the control silage. When the DM recovery results were combined with the feed per gain results, the silages with 1174 and experimental inoculant produced 5.3 and 10.5 lb more steer gain per ton of crop ensiled, respectively, than the control silage.
Keywords: Beef; Alfalfa; Silage; Inoculant; Preservation; Nutritive value